2020
DOI: 10.3389/fneur.2020.00613
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Auditory Effects of Traumatic Brain Injury and Blast Exposure in Service Members and Veterans

Abstract: Service members and veterans (SMVs) with a history of traumatic brain injury (TBI) or blast-related injury often report difficulties understanding speech in complex environments that are not captured by clinical tests of auditory function. Little is currently known about the relative contribution of other auditory, cognitive, and symptomological factors to these communication challenges. This study evaluated the influence of these factors on subjective and objective measures of hearing difficulties in SMVs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Anecdotal accounts from clinicians at the Veterans Affairs Pittsburgh Healthcare System (VAPHS) indicate that medical charts tend to include more notations of non-auditory comorbidities for Veterans with, rather than without, hearing complaints. Common comorbidities for Veterans with hearing complaints include blast-related traumatic brain injury (TBI; Callahan & Storzbach 2 ; Gallun et al 3,4 ; Kontos et al 5 ; Kuchinsky et al 6 ; Saunders et al 1 ), posttraumatic stress disorder (PTSD; Armenta et al 7 ; Callahan & Storzbach 2 ; Department of Veteran Affairs 8 ; Reavis et al 9 ), and other mental health illnesses such as depression and substance abuse (Department of Veteran Affairs 8 ; Jacobson et al 10 ; Thomas et al 11 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal accounts from clinicians at the Veterans Affairs Pittsburgh Healthcare System (VAPHS) indicate that medical charts tend to include more notations of non-auditory comorbidities for Veterans with, rather than without, hearing complaints. Common comorbidities for Veterans with hearing complaints include blast-related traumatic brain injury (TBI; Callahan & Storzbach 2 ; Gallun et al 3,4 ; Kontos et al 5 ; Kuchinsky et al 6 ; Saunders et al 1 ), posttraumatic stress disorder (PTSD; Armenta et al 7 ; Callahan & Storzbach 2 ; Department of Veteran Affairs 8 ; Reavis et al 9 ), and other mental health illnesses such as depression and substance abuse (Department of Veteran Affairs 8 ; Jacobson et al 10 ; Thomas et al 11 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hoover et al 15 ; Kontos et al 5 ; Kuchinsky et al 6 ; Martindale et al 16 ; Saunders et al 1 ). These auditory-related cognitive problems can manifest behaviorally as central auditory processing (CAP) deficits.…”
Section: Traumatic Brain Injury and Hearingmentioning
confidence: 99%
“…Earlier publications reported that the blast wave has more impact on ear first compare to other organs ( Cernak, 2010 ; Pham et al., 2015 ; Sundaramurthy et al., 2012 ; Lew et al., 2007 ). Hearing loss (HL) and tinnitus are highly prevalent in the growing population of returning soldiers, while no effective and safe treatment is revealed ( Lew et al., 2007 ; Kuchinsky et al., 2020 ; Chadha and Cieza, 2017 ). In United States, the occurrence of noise induced hearing loss among noise exposed population is 23% with hearing loss, 15% with tinnitus and 9% with both illnesses ( Masterson et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) have been applied for the past five decades in treating various disease condition ( Wu et al., 2014 ; Eshraghi et al., 2012 ). Specifically, stealth nanoparticles, C. Sun et al., encapsulated dexamethasone in PEG-coated PLA nanoparticles for delivering compounds to the cochleae ( Kuchinsky et al., 2020 ; Horie et al., 2010 ; Sun et al., 2016 ). Nanoparticle (NP)-have showed rewards of sustained release and comfort of surface modification, therefore the NP-based delivery systems have become a current research attention[ ( An and Zha, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss and tinnitus are among the most prevalent disabilities reported in veterans, and the incidence of hearing deficits in service members greatly exceeds that of the civilian population in the United States ( 1 ). Although auditory system damage from gunfire or weapon systems (e.g., artillery, mortars) has historically been the predominant cause of combat-related hearing loss, blast.…”
Section: Introductionmentioning
confidence: 99%